2015
DOI: 10.1158/1078-0432.ccr-14-1781
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Intravesical Mitomycin plus Bacillus Calmette–Guérin for Non–Muscle-Invasive Urothelial Bladder Carcinoma: Translational and Phase I Clinical Trial

Abstract: Purpose To determine the safety and toxicities of sequential MMC + BCG in patients with non-muscle invasive bladder cancer (NMIBC) and explore evidence for potentiation of BCG activity by MMC. Experimental Design A 3+3 phase I dose-escalation trial of six weekly treatments was conducted in patients with NMIBC. MMC (10, 20 or 40 mg) was instilled intravesically for 30 minutes, followed by a 10-minute washout with gentle saline irrigation and then instillation of BCG (half or full strength) for 2 hours. Urine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…At week 8 after the first MNU instillation and prior to the development of CIS or papillary tumors, rats received 6 weekly treatments with the following intravesical agents: 1) BCG, which is the standard of care for high risk NMIBC; 2) mitomycin C (MMC), which is the most commonly used intravesical chemotherapy; cisplatin, the most commonly used systemic chemotherapy for bladder cancer; and 3) the combination of BCG+MMC, which has has improved efficacy over BCG alone in clinical trials (22, 23). Histological examination showed that BCG-treated tumors had evidence of marked lymphocytic infiltrates not seen with other chemotherapeutic regimens (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At week 8 after the first MNU instillation and prior to the development of CIS or papillary tumors, rats received 6 weekly treatments with the following intravesical agents: 1) BCG, which is the standard of care for high risk NMIBC; 2) mitomycin C (MMC), which is the most commonly used intravesical chemotherapy; cisplatin, the most commonly used systemic chemotherapy for bladder cancer; and 3) the combination of BCG+MMC, which has has improved efficacy over BCG alone in clinical trials (22, 23). Histological examination showed that BCG-treated tumors had evidence of marked lymphocytic infiltrates not seen with other chemotherapeutic regimens (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have suggested that combining MMC and BCG may decrease recurrence and reduce progression for patients with NMIBC (11, 22, 23). It has been postulated that the mechanism for improved efficacy with combinatorial therapy is in transforming M2 associated macrophages toward a beneficial M1 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…5×10 5 TAMs were transfected with sh-Wnt5a or sh-NC for 8h and then washed 3 times with PBS, and subsequently cultured with 1ml fresh serum-free medium. After 24 hours, the cultured supernatant was harvested and centrifuged for 10 minutes at 10,000 r/min, which was defined as conditioned medium (CM).…”
Section: Conditioned Medium Collectionmentioning
confidence: 99%
“…In general, TAMs are mainly categorized into classically activated macrophages (M1 phenotype) and alternatively activated macrophages (M2 phenotype) [1,4]. M1-like TAMs, highly expressing HLA-DR, CD86, IL-1β, IL-12, IL-23 and INOS, are thought to induce inflammatory response and activate anti-tumor immune response, resulting in tumor suppression [5,6]. Whereas M2-like TAMs, of which representative markers are CD206, CD163, IL-10, TGFβ, CCL17, CCL18, CCL22 and Arg-1, exert anti-inflammatory activities and play a crucial role in promoting tumor invasion and metastasis [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, AE were not increased by the double interventions, suggesting that BCG did not exacerbate the AE caused by MAGE-A3 vaccination, and vice-versa. Although there are not yet clear predictive markers for BCG efficacy, some cytokines, chemokines and/or growth factors have been shown to be increased upon BCG in urine (19)(20)(21)(22). Therefore, to assess whether the immunomodulatory impact of BCG therapy was modified by MAGE-A3 vaccination, we measured in urine a selected panel of cytokines (IL-2, 6, 8, 10, 12, 15, 17, MIG, RANTES), chemokines (IP-10 and MIP-1b), and growth factors (GM-CSF, G-CSF; refs.…”
Section: Safety Of Combination Therapymentioning
confidence: 99%